2017
DOI: 10.1177/0192623317735776
|View full text |Cite
|
Sign up to set email alerts
|

In Search of a Converging Cellular Mechanism in Nanotoxicology and Nanomedicine in the Treatment of Cancer

Abstract: Multiple applications of nanomaterials have raised concern with regard to their toxicity. With increasing research into nanomaterial safety, mechanisms involved in the toxic effects of nanomaterials have begun to emerge. The importance of nanomaterial-induced lysosomal membrane permeabilization through overloading or direct damage of the lysosomal compartment, resulting in the blockade of autophagosome-lysosome fusion and autophagy dysfunction, as well as inflammasome activation were cited as emerging mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 126 publications
0
7
0
Order By: Relevance
“…[ 38 ] At present, many studies reported that engineered nanomaterials could result in lysosomal dysfunction and cause autophagy processes under a toxic dose. [ 39,40 ] Moreover, several research works also suggested that AgNPs could give rise to autophagy in different conditions. [ 41,42 ] However, more investigations should be made to explain the autophagic regulation by AgNPs under sublethal dose.…”
Section: Discussionmentioning
confidence: 99%
“…[ 38 ] At present, many studies reported that engineered nanomaterials could result in lysosomal dysfunction and cause autophagy processes under a toxic dose. [ 39,40 ] Moreover, several research works also suggested that AgNPs could give rise to autophagy in different conditions. [ 41,42 ] However, more investigations should be made to explain the autophagic regulation by AgNPs under sublethal dose.…”
Section: Discussionmentioning
confidence: 99%
“…The key mechanisms of pinocytosis, which are involved in nanoparticle uptake include micropinocytosis, clathrin-mediated endocytosis, caveolae-mediated endocytosis, and clathrin-and caveolae-independent endocytosis [158]. Ultimately, most of their endocytic pathways lead to contents ending up in lysosomes for degradations [159]. However, in caveolae-mediated endocytosis, from endosomes, the contents form caveosomes, which are transported to the endoplasmic reticulum/Golgi apparatus, avoiding lysosomal degradation.…”
Section: Cellular Binding and Persistencementioning
confidence: 99%
“…However, in caveolae-mediated endocytosis, from endosomes, the contents form caveosomes, which are transported to the endoplasmic reticulum/Golgi apparatus, avoiding lysosomal degradation. This nuance in the uptake mechanisms was discovered as an important consideration for tailoring nanocarriers with drugs in cancer therapy [159].…”
Section: Cellular Binding and Persistencementioning
confidence: 99%
“…Similarly, Song, Du, Feng, Wu, and Yan (2013) demonstrated the induction of pyroptosis by ZnO NPs via the caspase‐1 pathway in A549 lung cancer cells. The importance of NM‐induced pyroptosis in immunotherapy is scarce and it has been suggested that the toxicological mechanisms of NMs involving LMP, inflammasome activation, and pyroptosis be considered as a potential research area in cancer therapy (Gulumian & Andraos, 2018). Indeed, LMP could activate pyroptosis via caspase‐1 and NLRP3 inflammasome activation (Repnik, Česen, & Turk, 2014).…”
Section: Nms Exhibiting Inherent Anti‐cancer Propertiesmentioning
confidence: 99%